2011
DOI: 10.2739/kurumemedj.58.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotionally Affect Adult and Baby’ Photographs in Healthy Controls and Schizophrenic Patients Evaluating by Exploratory Eye Movements

Abstract: Humans obtain a particularly large amount of information for adapting to their environment visually as opposed to other types of sensory input. Specific information is selected from a wide variety of visual stimuli, and then processed to guide behavior. Affection and emotion are critical elements of human relationships: generally, negative emotions impair quality of life, while positive emotions make life pleasurable. Affective stimuli have been shown to influence event-related potentials such as P300 componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In a previous study, Nishiura et al [9] reported that viewing images with positive content reduced left TNGP in schizophrenia. Moreover, we also reported that the left TNGP was smaller in schizophrenic patients under positive affect with voice [11]. The present finding that TNGP was significantly smaller and did not recover after the second viewing of smiling babies only in the left field is consistent with previous findings of abnormal left field scanning in schizophrenia during viewing of positive emotional stimuli.…”
Section: Total Number Of Gaze Points (Tngp)supporting
confidence: 82%
See 1 more Smart Citation
“…In a previous study, Nishiura et al [9] reported that viewing images with positive content reduced left TNGP in schizophrenia. Moreover, we also reported that the left TNGP was smaller in schizophrenic patients under positive affect with voice [11]. The present finding that TNGP was significantly smaller and did not recover after the second viewing of smiling babies only in the left field is consistent with previous findings of abnormal left field scanning in schizophrenia during viewing of positive emotional stimuli.…”
Section: Total Number Of Gaze Points (Tngp)supporting
confidence: 82%
“…It has been reported that schizophrenic patients have a dysfunction in left eye scanning [8][9][10][11]. Healthy controls first scan the left field of a screen, but schizophrenic patients were found to hardly scan the left field at all.…”
mentioning
confidence: 99%